2014
DOI: 10.1111/nph.12961
|View full text |Cite
|
Sign up to set email alerts
|

Land use influences arbuscular mycorrhizal fungal communities in the farming–pastoral ecotone of northern China

Abstract: Summary We performed a landscape‐scale investigation to compare the arbuscular mycorrhizal fungal (AMF) communities between grasslands and farmlands in the farming–pastoral ecotone of northern China. AMF richness and community composition were examined with 454 pyrosequencing. Structural equation modelling (SEM) and multivariate analyses were applied to disentangle the direct and indirect effects (mediated by multiple environmental factors) of land use on AMF. Land use conversion from grassland to farmland s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 67 publications
15
110
1
1
Order By: Relevance
“…Plant and soil samples were collected according to the methods described by Xiang et al (2014). At each sampling site, four 1 × 1 m 2 quadrats were designated for vegetation survey.…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Plant and soil samples were collected according to the methods described by Xiang et al (2014). At each sampling site, four 1 × 1 m 2 quadrats were designated for vegetation survey.…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Similarly, in Northern China, Xiang et al (2014) found that the land use influence on AMF community composition was mediated by soil properties at a landscape-scale. Hazard et al (2013), by using Trifolium repens and Lolium perenne bait plants to compare AMF communities in the soil of 40 geo-graphically dispersed sites in Ireland representing different land uses and soil types, found that AMF community compo-sition was influenced by abiotic variables (pH, rainfall, and soil type), but not land use or geographical distance, suggest-ing that specific environmental variables of sites that differ within land uses have a stronger effect than land use itself on AMF communities.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these specific environmental factors, direct land use-related circumstances, such as tillage (which in-creases soil disturbance) or grazing (which removes above-ground plant biomass), also have been suggested as drivers of AMF community composition (e.g., Helgason et al 1998;Oehl et al 2010;Schnoor et al 2011;Stockinger et al 2014;Valyi et al 2015). A high number of studies specifically have addressed the impact of agricultural practices and changes in land use on either the composition of AMF communities (e.g., van der Gast et al 2011;Lin et al 2012;Lumini et al 2010;Verbruggen et al 2012;Dai et al 2013;Hazard et al 2013;Morris et al 2013;Moora et al 2014;Xiang et al 2014;Valyi et al 2015) or individual taxa (Bainard et al 2014;Jansa et al 2014). Experimental studies, however, usually are confined to one or a few sites, and therefore may have facilitated the identification of effects of specific agricultural practices at the expense of visibility of other (independent) effects such as soil type and geography (Jansa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased precipitation could significantly increase AM fungal root colonisation rate, spore density, and ERH density, decrease AM fungal diversity, and changed AM fungal community composition in grassland ecosystems (Li et al 2015; Gao et al 2016). Land use conversion from grassland to farmland significantly reduced soil AM fungal ERH density and richness, and altered AM fungal community composition (Xiang et al 2014). In addition, grass ( Elymus nutans, Avena sativa , and Vicia sativa ) plantation affected rhizosphere soil AM fungal ERH density, richness and community composition (Zheng et al 2016b).…”
Section: Mycorrhizal Fungal Response To Global Changementioning
confidence: 99%